A study on agv battery performance affecting factors in manufacturing environment - Maharof, Madihah (2013)
Material Handling System (MHS) is the backbone of a Flexible Manufacturing System (FMS). AGV is most often used in MHS industrial applications to move materials around manufacturing facility. AGV is unmanned vehicles that usually run on predefined guide paths in large material warehouses to transport goods among different workstations. This project focuses on the factors AGV battery performance affecting in manufacturing environment. When dealing with AGV in factories, many important factors need to be considered in order to ensure that the AGV will works efficiently and the life of the AGV battery itself is one of the crucial parts to maintain and control. Usually, when AGV is running and working smoothly in production lines, the battery condition need to be always monitored and it is necessary to take into account that the use of battery may impact the performance of the overall system. In this study and analysis, the factors of load and no load are considered. During data collection, AGV is running with both of factors in two conditions which are with stoppage and without stoppage, assuming that stoppage condition happen due to the existence of obstacles such as human, forklift, and etc. When AGV is running on the path within 15 minutes, without load and without stoppage gives more effect to the battery deterioration. It used 39.17% of battery to move the AGV compared to when AGV is working with load and without stoppage which used only 23.34% of battery.